Evaluating eruption of central incisors and first molars in relation to age and sex - J. Mahmodian; Sh. Banakar (Tehran University of Medical Sciences, 1992)
Eruption is a developmental process in 3 phases of pre-eruptive, prefunctional and functional. Until now there has not been any research on the relationship between eruption and sex and age in Iran in order to compare with the available standards. In This study we recruited 3174 children of 5-8.28 years and eruption sequence in them was evaluated. The results showed that eruption is slightly sooner in girls in comparison to boys which is not statistically significant. The percentage of erupted teeth will increase by increasing age but Maxillary central incisors in boys are the exception. In addition, molars are erupted prior to mandibular centrals.